Les déterminants individuels de comportement organisationnel dans l’organisation – perception et apprentissage - - allalga, zohir (Journal of Social Sciences and Humanities, 2022)
A group of factors involved in industrial establishment in shaping the individual behavior in the organization ,they are called individual determinants of organizational behavior ,as this study aims to uncover the correlation relationship between the( perception - social learning) and the organization behavior, and identify the level of the organization’s interest in developing behavior ,where This study is conducted at the (Mines de Fer de l’Est) on a sample of (112), single, and by using the descriptive analytical method and a research questionnaire tool, and by applying the statistical program "SPSS", with a group of Statisticprogram "SPSS", with a group of Statistical methods such as the Pearson coefficient , or so-called chi-squared(tabular and calculated values) , with an other set of values ,such as the level of significance , degree of freedom , observed frequencies ,and expected frequencies , to test the hypotheses of the study, -There is a statistically significant correlation relationship between the (perception) And the organizational behavior . - there is a statistically significant correlation relationship between the social learning and the organizational behavior - the level of interest of the institution by developing organizational behavior is high.The results of hypothesis testing and data analysis of this study confirmed the- existence of astatistically significant correlation relationship between the perception and behavior - existence of astatistically significant correlation relationship between the learning and behavior The level of the institution’s interest in developing the behavioral